2022
DOI: 10.4995/ijpme.2022.16807
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable and agile manufacturing outsourcing partner selection: a literature review

Abstract: Outsourcing to third party to manage non-core activities helps the firm to focus on core activities. Manufacturing firms are outsourcing product development, manufacturing, logistics, customer care etc. to enhance production capacity and flexibility, and to reduce operational costs, which in turn can improve profitability and competitive advantage of the enterprise. Sustainability in operations and supply chain is gaining momentum due to increased global environmental concern, pressures from consumers and comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 90 publications
0
6
0
Order By: Relevance
“…Financial indicators such as net profits, return on assets, return on equity and return on investments are key determinants of performance. The non-financial measures such as customer base, market share and employee retention supplement the financial measures (Akhtar, 2022). The study recommended that firms outsource essential services and products not produced internally.…”
Section: Stratford Peer Reviewed Journals and Book Publishing Journal...mentioning
confidence: 99%
“…Financial indicators such as net profits, return on assets, return on equity and return on investments are key determinants of performance. The non-financial measures such as customer base, market share and employee retention supplement the financial measures (Akhtar, 2022). The study recommended that firms outsource essential services and products not produced internally.…”
Section: Stratford Peer Reviewed Journals and Book Publishing Journal...mentioning
confidence: 99%
“…Zhou and Yuen (2021) proposed optimal remanufacturing strategy through contract manufacturer or independent remanufacturer for original equipment manufacturer. Akhtar (2022) carried out literature review of agile and sustainable MOP selection. Lahiri et al (2022) carried out meta-analysis of 106 primary studies from 1992 to 2019 to examine the effect of industrial nature of activity (manufacturing vs. services), value chain activity (core vs. non-core) and provider's location (domestic vs. international) in sourcing on firm performance and found that outsourcing has positive relationship with firm performance for non-core and international outsourcing equally manufacturing and service sector.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Zhou and Yuen (2021) proposed optimal remanufacturing strategy through contract manufacturer or independent remanufacturer for original equipment manufacturer. Akhtar (2022) carried out literature review of agile and sustainable MOP selection. Lahiri et al .…”
Section: Literature Reviewmentioning
confidence: 99%
“…As consumers continue to be concerned about the origin and safety of the products they purchase, SC operations must ensure that they have end-to-end visibility of their SC, from the source of the raw materials to the delivery of the final product to the customer. This requires collaboration between all parties in the SC, as well as the use of technologies such as blockchain, which can provide a secure and transparent way to track the movement of goods (Akhtar, 2022). Moreover, in the post-COVID world, SCs must be prepared to quickly adapt to changing consumer preferences, disruptions in transportation, and other unforeseen events to ensure the continued availability of essential goods and services.…”
Section: Bij 315mentioning
confidence: 99%